The Impact of Transformational Leadership and Creative Partnerships on Innovation Dynamics and Organizational Performance - Kifni Yudianto; Maria Valeria Roellyanti; Arif Fakhrudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to investigate and uncover the important role of transformational leadership as well as the dynamics of creative partnerships in an organizational context. The main focus of the study is to identify the impact generated by the interaction between transformational leadership and creative partnerships on innovation levels and organizational performance. This study used a quantitative approach. Cross-sectional research designs are used to evaluate relationships between variables. The study population was members of business organizations spanning different levels of office. The study sample consisted of 120 respondents randomly selected from the population. Distribution of questionnaires online or in person to selected respondents, by providing clear instructions to respondents regarding filling out questionnaires. The collected data is processed using Structural Equation Modeling (SEM) through AMOS software. The results show that transformational leadership is significantly associated with creative partnership dynamics, innovation, and organizational performance. The dynamics of creative partnerships are also significantly related to innovation. However, the relationship between creative partnership dynamics and organizational performance was not significantly confirmed. The findings reinforce the importance of leaders' roles in creating work environments that support collaboration and creativity. In addition, the significant relationship between Innovation and Organizational Performance emphasizes the importance of innovation in improving overall performance. In addition, organizations should pay attention to transformational leadership development to drive innovation and better performance. Leadership training that focuses on the ability to inspire, support, and facilitate creative collaboration can be an effective strategy.